Valuation of American Call Option Considering Uncertain Volatility (Advances in Applied Mathematics and Mechanics, 2010)
The parabolic variational inequality for simulating the valuation of American option is used to analyze a continuous dependence of thesolution with respect to the uncertain volatility parameter. Three kinds of the continuity are proved, enabling us to employ the maximum range method for the uncertain parameter, under the condition that the criterion-functional has the corresponding property.